To study prevalence of incipient iron deficiency in primary hypothyroidism - Banday, Tanveer Hassan; Bhat, Sadaf Bashir; Bhat, Sabreen Bashir; Shah, Naveed; Bashir, Shahnawz (International Journal of Research in Medical Sciences, 2017)
Background: Hypothyroidism, affects around 1% of general population. Anemia in association with hypothyroidism has been studied since 1881. Iron deficiency has multiple adverse effects on thyroid metabolism. It decreases circulating thyroid hormone concentration, blunts thyrotrophic response to TRH, decreases serum T3. Objective of current study was to find prevalence of iron deficiency in primary hypothyroid. Methods:In our study 70 patients were selected, out of which 50 were females and 20 were males, who were suffering from hypothyroidism. Iron deficiency in the study group was confirmed at baseline using multiple iron status indicators (serum ferritin, serum iron, TIBC & percentage Saturation). These patients were between age group 18-65 years. Results: In our study only 14 patients (20%) manifested with anemia (which was defined as Hb<12gm/dl), where as the prevalence of iron deficiency (with or without anemia) was 34.2%, in which 28.5% were females and 5.70% were males, thus showing that prevalence of iron deficiency (with or without anemia) can be higher than iron deficiency anemia itself, which is supported by literature. Conclusion:Iron deficiency was present in a significant portion of patients with primary hypothyroidism. It also concluded that frequency of iron deficiency (with or without anemia) was higher than iron deficiency anemia.